LPS Stimulation Induces Small Heterodimer Partner Expression Through the AMPK-NRF2 Pathway in Large Yellow Croaker (Larimichthys crocea) - Du, Jianlong; Xiang, Xiaojun; Xu, Dan; Cui, Kun; Pang, Yuning; Xu, Wei; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2021)
Small heterodimer partner (SHP) plays an important regulatory role in inflammation in mammals. The main objective of this study was to investigate the response of SHP to inflammatory stimulation and the underlying mechanism. In the present study, the shp gene was cloned from large yellow croakers, which was mainly expressed in the liver and intestine. The results showed that LPS stimulation induced the mRNA expression and protein level of SHP in macrophages of large yellow croakers. Overexpression of SHP significantly decreased mRNA expression of tnfα, il-1β, il-6 and cox2 induced by LPS treatment in macrophages. Further investigation found that LPS stimulation increased the phosphorylation level of AMPK in macrophages. AMPK inhibitor treatment significantly decreased the expression of SHP induced by LPS while AMPK activator significantly increased the expression of SHP. Furthermore, results showed that nuclear factor erythroid-2 related factor 2 (NRF2) increased the promoter activity of SHP in large yellow croakers and the level of nuclear NRF2 was increased by LPS stimulation and AMPK activation. In addition, NRF2 inhibitor treatment significantly decreased mRNA expression of shp induced by LPS and AMPK activator. In summary, the present study showed that LPS can induce SHP expression by activating the AMPK-NRF2 pathway while SHP could negatively regulate LPS-induced inflammation in large yellow croakers.